The Wheel of Women: Global Female Artists Expound Lifecycle Themes through 'Calendar' - Min, Si (Pacific International Journal, 2024)
Since the emergence of the second wave of feminism in the late 1960s, feminist scholars have significantly influenced the study of visual culture, while female artists have made notable strides in exploring form, subject matter, and avant-garde expression. This paper examines the utilization of the "Calendar" motif by several feminist artists as a symbol representing the passage of time. Through this visual language, these artists convey themes intricately linked to the female experience, such as growth, change, maturity, and aging. Their transformative approach extends beyond mere subjects and artistic techniques to encompass a unique perspective characterized by the liberation from external viewpoints and the male-dominated gaze, redirecting attention to the inner world of women. In doing so, female artists offer a nuanced and profound exploration of humanity, emotions, and life experiences, transcending simplistic gender labels and feminist advocacy. The paper explres the evolution of Calendar paintings, shedding light on their depiction of historical and aesthetic shifts in Chinese society. Serving as a hallmark of its era, the Calendar not only chronicles the progression of national capitalism but also mirrors the cultural metamorphosis of old China. Furthermore, the paper explores contemporary female artists' engagement with cyclical themes, illustrating how they navigate the life cycle, natural rhythms, and women's experiences across diverse mediums. Finally, the author's photographic creation is discussed, offering reflections on Chinese women's pursuit of autonomy amidst the interplay of tradition and modernity.